National Human Research Ethics: A Preliminary Comparative Case Study of Germany, Great Britain, Romania, and Sweden. Issue 7 (2nd October 2016) - Gallagher, Bernard; Berman, Anne H.; Bieganski, Justyna; Jones, Adele D.; Foca, Liliana; Raikes, Ben; Schiratzki, Johanna; Urban, Mirjam; Ullman, Sara
Abstract : Although international research is increasing in volume and importance, there remains a dearth of knowledge on similarities and differences in "national human research ethics" (NHREs), that is, national ethical guidelines (NEGs), Institutional Review Boards (IRBs), and research stakeholder' ethical attitudes and behaviors (EABs). We begin to address this situation by reporting upon our experiences in conducting a multinational study into the mental health of children who had a parent/carer in prison. The study was conducted in 4 countries: Germany, Great Britain, Romania, and Sweden. Data on NHREs were gathered via a questionnaire survey, two ethics-related seminars, and ongoing contact between members of the research consortium. There was correspondence but even more so divergence between countries in the availability of NEGs and IRBs and in researcher' EABs. Differences in NHREs have implications particularly in terms of harmonization but also for ethical philosophy and practice and for research integrity.